2023
DOI: 10.1021/acssynbio.3c00014
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Transcription/Translation-Coupled DNA Replication through Partial Regeneration of 20 Aminoacyl-tRNA Synthetases

Abstract: The in vitro reconstruction of life-like self-reproducing systems is a major challenge in in vitro synthetic biology. Self-reproduction requires regeneration of all molecules involved in DNA replication, transcription, and translation. This study demonstrated the continuous DNA replication and partial regeneration of major translation factors, 20 aminoacyl-tRNA synthetases (aaRS), in a reconstituted transcription/translation system (PURE system) for the first time. First, we replicated each DNA that encodes on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Despite the inhibition, DNA replication still reached approximately 40fold, which is sufficient to maintain a constant concentration in serial dilution experiments performed in previous studies. 27,29,30 Furthermore, the increased transcription and translation are beneficial for the construction of a selfregenerating system, which is one of the next important targets in the field of in vitro synthetic biology 31,33 and requires the synthesis of large amounts of RNA and proteins. The results obtained in this study provide useful knowledge and methods to achieve a self-regenerating artificial system in the future.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the inhibition, DNA replication still reached approximately 40fold, which is sufficient to maintain a constant concentration in serial dilution experiments performed in previous studies. 27,29,30 Furthermore, the increased transcription and translation are beneficial for the construction of a selfregenerating system, which is one of the next important targets in the field of in vitro synthetic biology 31,33 and requires the synthesis of large amounts of RNA and proteins. The results obtained in this study provide useful knowledge and methods to achieve a self-regenerating artificial system in the future.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The in vitro reconstitution of cellular functions has proven to be a useful approach for understanding living systems and developing new biotechnologies. One of the central functions of the cell is the replication and expression of genetic information, known as the central dogma, which comprises three reactions: transcription, translation, and DNA replication. These reactions have been partially reconstituted in vitro , both independently and in combination. However, their efficiency is still far from being comparable to that in living cells, especially for the combined reaction, which hinders the development of a self-sustaining artificial system. , …”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been achieved that the elements of protein synthesis are expressed by the PURE system. 7,38,39 Elements for cell division such as membrane proteins and spatiotemporal regulators for the cell division plane are also synthesized by the PURE system in liposomes. 12,40−42 However, the conventional PURE system used in these studies lacks metabolic pathways, which are the other essential systems for self-reproduction.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Recent numerous attempts have reconstituted cellular functions using the PURE system. For example, it has been achieved that the elements of protein synthesis are expressed by the PURE system. ,, Elements for cell division such as membrane proteins and spatiotemporal regulators for the cell division plane are also synthesized by the PURE system in liposomes. , However, the conventional PURE system used in these studies lacks metabolic pathways, which are the other essential systems for self-reproduction. Since glycolysis is the most upstream metabolic pathway, the coupling between glycolysis and protein synthesis serves as a fundamental supplier of elements for self-replication such as phospholipids, amino acids, and nucleic acids as well as the role of ATP and NADH regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in the quest for the minimal synthetic cell have been substantial, especially in critical areas such as physicochemical homeostasis, DNA replication, membrane growth, , and membrane scission. , The emerging synthetic cell will ultimately harness its own gene expression machinery to regulate these complex features. In vitro transcription-translation (in vitro transcription and translation (IVTT)) is a well-established technology for the synthesis of proteins from plasmids and linear DNA encoding for a small number of genes. Previous reports on phage genomes and large plasmids have shown that it is possible to express in the order of tens to a few hundred genes using DNA templates longer than 100 kbp. , Whereas these examples are excitingly close to a formerly postulated minimal genome (113 kbp with 151 genes), top-down experimental work on Mycoplasma established that the current minimal synthetic genome requires at least 493 genes. , From a bottom-up perspective, it is conceivable that the construction of synthetic cells requires similarly sized genomes, and these will need to be expressed in vitro.…”
Section: Introductionmentioning
confidence: 99%